1995
DOI: 10.1086/647041
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Colonization with Vancomycin-Resistant Enterococcus Faecium

Abstract: VREF colonization is at least 10-fold more prevalent than infection among oncology patients. Colonization often persists throughout lengthy hospitalizations and may continue for long periods following hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
97
4
6

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(116 citation statements)
references
References 26 publications
9
97
4
6
Order By: Relevance
“…It has been demonstrated that colonisation with the same strain of VRE may persist for at least a year [20,30,35] and that there is a signi®cant association between gastro-intestinal colonisation and the subsequent development of invasive infection [6, 10, 20, 30± 32]. Colonisation rates appear to be ten times more prevalent than infection rates [16,20,30].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been demonstrated that colonisation with the same strain of VRE may persist for at least a year [20,30,35] and that there is a signi®cant association between gastro-intestinal colonisation and the subsequent development of invasive infection [6, 10, 20, 30± 32]. Colonisation rates appear to be ten times more prevalent than infection rates [16,20,30].…”
Section: Discussionmentioning
confidence: 99%
“…Although Enterococcus faecalis is the most prevalent species causing invasive enterococcal infection, E. faecium has been reported as the species accounting for most glycopeptide resistant infection, in particular E. faecium strains with the Van A resistance phenotype [10,14,19,20,27,30,35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to data from the National Nosocomial Infections Surveillance System, by the end of 1999 about 25% of all enterococci involved in nosocomial infections were vancomycin resistant (1). Once colonized, patients become long-term carriers (2). Patients can be colonized with VRE before they are actively infected with such organisms, and, once infected, mortality is increased (3).…”
mentioning
confidence: 99%